Respuesta :
Step-by-step explanation:
Step 1: Subtract 4x from both sides
[tex]2x^2 - 4x = 4x - 4x - 7[/tex]
[tex]2x^2 - 4x = -7[/tex]
Step 2: Add 7 to both sides
[tex]2x^2 - 4x + 7 = -7 + 7[/tex]
[tex]2x^2 - 4x + 7 = 0[/tex]
Step 3: Use the Quadratic Formula
[tex]x = \frac{ -b \pm \sqrt{b^2 -4ac} }{2a}[/tex]
[tex]x = \frac{ -(-4) \pm \sqrt{(-4)^2 - 4(2)(7)} }{ 2(2 )}[/tex]
[tex]x = \frac{ 4 \pm \sqrt{-40} }{4}[/tex]
[tex]x = \frac{4 \pm2i \sqrt{10} }{4}[/tex]
[tex]x = \frac{2 \pm i\sqrt{10}}{2}[/tex]
Answer: [tex]x = \frac{2 \pm i\sqrt{10}}{2}[/tex]